2021
DOI: 10.1002/mds.28614
|View full text |Cite
|
Sign up to set email alerts
|

Scoring Algorithm‐Based Genomic Testing in Dystonia: A Prospective Validation Study

Abstract: Despite the limitations, including a short follow-up period and small sample size, this pilot study suggests that FUS Vo-thalamotomy may be an alternative treatment option for patients with FHD. A randomized controlled study with a larger sample size and a longer follow-up period is warranted to elucidate the efficacy and safety of MRgFUS Vo-thalamotomy for FHD.Acknowledgments: We thank Kaoru Shimizu from the Intelligent Clinical Research and Innovation Center at the Tokyo Women's Medical University for her in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 23 publications
(32 reference statements)
2
7
0
Order By: Relevance
“…For detailed clinical characteristics and a review of previously reported cases, see Table 1 and Supplementary Table 3. Genotype information from families 1 and 2 has been published previously [11,12].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For detailed clinical characteristics and a review of previously reported cases, see Table 1 and Supplementary Table 3. Genotype information from families 1 and 2 has been published previously [11,12].…”
Section: Resultsmentioning
confidence: 99%
“…Genetic studies in families 1 and 2 have been described [11,12]. WES on genomic DNA isolated from the blood lymphocytes of the subjects in families 3 and 4 was carried out using previously reported methods [13].…”
Section: Genetic Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, our diagnostic approach is the first algorithm that covers all forms of adult-onset dystonia, including acquired, neurodegenerative and genetic causes. The recommendation to refrain from further investigations in patients with AOIFD at step 5 of our algorithm, is in line with a recently introduced scoring algorithm for dystonia, predicting the diagnostic utility of genetic testing by using WES 49. According to this prediction tool, which was based on a large exome-wide study,50 an AOIFD-phenotype will lead to a sum score of 0 or 1 points, indicating that genetic testing is not recommended.…”
Section: Discussionmentioning
confidence: 70%
“…According to this prediction tool, which was based on a large exome-wide study,50 an AOIFD-phenotype will lead to a sum score of 0 or 1 points, indicating that genetic testing is not recommended. Both in the prediction tool49 as in our algorithm the clinical characteristics ‘age at onset’, ‘body distribution’ and ‘associated features’ are incorporated. However, in the criteria of the prediction tool ‘temporal pattern’ is not included and no distinction is made between typical (Table 1) and atypical dystonias, such as focal leg dystonia which can be an important clue for an underlying inherited condition, or lead to a diagnosis of an acquired or neurodegenerative disorder earlier in the diagnostic process.…”
Section: Discussionmentioning
confidence: 99%